Didactic Opportunities for Developing Students' Natural Scientific Worldview (International Journal of Scientific Trends, 2025)
The article discusses the design of electronic educational programs for students in natural sciences based on the humanistic paradigm of education, according to which the student is not a passive consumer of knowledge, but an active subject of the educational process. Analysis of student needs; setting learning goals; selection and systematization of content; determination of forms, methods and means of education; development of interface and interaction logic; assessment of educational effectiveness.